AKSES INTERNET DAN PRESTASI HAFALAN ALQURAN - Darman Fauzan Dhahir (Balai Diklat Keagamaan Bandung, 2020)
The activity of memorizing Quran has been a custom of Muslims since the time of Prophet Muhammad May Peace be upon Him. When the internet developed and became an inseparable part of human life, it was feared to harm the achievement of Quran memorizing. To prove the truth of that concern, this quantitative research was conducted. The research is aimed at measuring the relationship between the duration and variety of internet access with the achievements of hafidz Quran (memorizers). The data are obtained by survey, interviews, and documentation, then analyzed statistically, presented and interpreted descriptively. The results show that internet access’ duration, and its utilization, such as processes, contents, and social forms have significant and positive relationships towards the achievement of the hafidz. On the other hand, the internet use intended for fun or as an escape to release stress does not have a significant relationship with the performance of the hafidz. Keywords: internet access; internet usage; Quran memorization